PRACTICAL LINGUISTICS: THE CONCEPT OF CREATING ELECTRONIC DICTIONARIES (Scientific journal of the Fergana State University, 2023)
The article will focus on the presence of positive and negative aspects of using traditional and electronic dictionaries. As the dynamics of the need for an electronic dictionary in applied linguistics grows, the demand for the formation of certain concepts of it increases. This contributes to the correct use of word forms that exist in the reference language, especially in the process of learning foreign languages. In addition, the article reflects the processes of dividing dictionaries into separate areas of application, bringing them to the electronic form. dictionary.